Talking politics, talking forgiveness - Barnes, Philip (Scottish journal of theology, 2011)
The aim of this article is to provide a provisional review and evaluation of recent Christian endorsements of the notion of political forgiveness. Attention is given to the doctrine of forgiveness in the New Testament and to its distinctive theological grammar. The chief theological features of Christian accounts of political forgiveness are outlined, before a number of weaknesses in the literature are identified and discussed. The implication of our discussion is that Christian love is expressed in two different ways, that of forgiveness upon repentance within the church and that of justice tempered by mercy in the socio-political realm.